Penguatan Sumber Daya Manusia melalui Sosialisasi Hukum Penyebaran Berita Hoax di PT. Mitsubishi Dipo Medan - Gebi Yohana P Panggabean; Junaidi Lubis (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
The dissemination of hoaxes in the digital era has expanded from social domains to private corporate sectors, posing serious threats to brand reputation and industrial relations. This community service (PKM) activity aims to educate and elevate the legal awareness of employees at PT. Mitsubishi Dipo Medan regarding the multi-layered legal consequences of spreading false news, encompassing cyber criminal law, civil law, and labor law. The community partners are employees across two major branches of PT. Mitsubishi Dipo Medan, namely the Sisingamangaraja Branch and the Krakatau Branch. Program implementation methods included interactive lectures, judicial case studies, and legal dispute simulations, evaluated via pre-test and post-test questionnaires aligned with the Ministry of Communication and Informatics’ digital literacy pillars. The results demonstrated a significant 109.4% increase in the participants' legal comprehension. The deep legal analysis examines the implications of the 2024 EIT Law amendment, the annulment of false news provisions in Law 1/1946 by the Constitutional Court through Decision Number 78/PUU-XXI/2023, the enforcement of the New Criminal Code (Law 1/2023) in 2026, and the application of civil vicarious liability doctrines under Article 1367 of the Indonesian Civil Code. The outcome of this program is the formation of a corporate internal risk mitigation framework through recommendations for updating Company Regulations and implementing Non-Disclosure Agreements to protect the automotive business stability of the partner.